Juvenile development of Callinectes danae Smith, 1869 ( Crustacea, Decapoda, Brachyura, Portunidae) under laboratory conditions - Bolla, Eduardo A. [UNESP]; Fransozo, Vivian; Negreiros-Fransozo, Maria Lucia [UNESP] (Acad Brasileira de Ciências, 2014)
The juvenile development of Callinectes danae was investigated from megalopae obtained in neuston samples at Ubatuba, Sao Paulo, Brazil. The individuals were raised in the laboratory under constant temperature ( 25 +/- 1 C), filtered sea water from the collection location (35%), and natural photoperiod. Newly hatched Artemia sp. nauplii were offered as food on a daily basis and ornamental-fish food was also provided for the juveniles from the 4(th) stage on. Twelve stages of the juvenile phase were obtained. The main morphological features that allowed recognition of the first juvenile stage were drawn and described. All the subsequent stages obtained were examined and measured, and the main changes in relation to the first stage were recorded. Sexual dimorphism becomes apparent from the fourth juvenile stage onwards. Some appendages and morphological features proved to be of great importance in the identification of species, including the number of segments of the antennal flagellum and the number of setae on the maxilla and on the 1(st), 2(nd) and 3(rd) maxillipeds. These can probably be used for future comparisons and species identifications.
Keywords: juvenile stages; morphology; portunid; post-larval; swimming